Generation Z’s Brand Love for Skincare Products: Do Religious Beliefs Matter? - Waluyo Waluyo; Rina Sari Qurniawati; Yulfan Arif Nurohman (Shirkah: Journal of Economics and Business, 2023)
To date, there has been no prior research examining the relationship between brand love as a determinant of brand loyalty and e-WOM specifically for halal skincare products. This study investigates how Muslim Generation Z might love a brand because of their religious beliefs and brand identity, resulting in brand loyalty and e-WOM that benefits the company. The questionnaire for this study was completed online by 120 participants from three cities in Central Java, Indonesia, namely Semarang, Salatiga, and Surakarta. The model was tested using PLS-SEM. The results of the research revealed that religious beliefs and brand identification affected brand love, whereas brand love affected brand loyalty and e-WOM. From this research, it can be seen that branding cannot be separated from faith. Muslims like brands that reflect their religious values and allow them to identify as Muslims. Therefore, marketers must have a comprehensive understanding of the halal concept in the manufacturing and production processes of halal skincare.